Very-small-aperture 3-D infrasonic array for volcanic jet observation at Stromboli Volcano - Yamakawa, Kazuya; Ichihara, Mie; Lacanna, Giorgio; Sánchez, Claudia; Ripepe, Maurizio (Geophysical journal international, 2022)
SUMMARY This study tested a very-small-aperture 3-D (VSA-3D) infrasonic array. A 3-D array is ideal for resolving the back elevation angle (BEL), which has become important in the analysis of volcanic jet noise or geological flows on steep mountain slopes. Although a VSA infrasonic array, with an aperture as small as a few tens of metres, has recently been shown to have a sufficient resolution of the backazimuth (BAZ) of incident signals, its BEL resolution is considered to be poor. We performed a four-element 3-D array experiment with a 20-m aperture and 2-m height at the summit of Stromboli Volcano. We analysed the direction of arrival (DOA) with the MUSIC algorithm as a function of frequency and conducted a cluster analysis for the estimated DOA–frequency functions of eruption signals. As a result, individual infrasonic signals were successfully related to eruptive vents. We also calculated the standard deviation (STD) of the DOAs in each cluster. Of the observed BAZ-STDs and BEL-STDs, 80 per cent were <2.0° and <4.6°, respectively. A comparison among the array geometries showed that the installation of a sensor above the ground, even at only 2 m, improved the BEL resolution, indicating that the VSA-3D array provides more detailed information about the wavefield than a planar array. The observed signals had higher BELs (−20° to 0°) than the vent direction (−30° to −25°) at 3–6 Hz, although signals above 20 Hz arrived from the vent direction. Our array verified that such DOA deviations were significant by the STD analysis and some tests with synthetic data. We infer that the DOA deviations do not indicate the source location and are caused by topographical diffraction.